2010
DOI: 10.1089/oli.2009.0216
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetics of Molecular Imaging Nanoparticles for mRNA Detection Determined in Tumor-Bearing Mice

Abstract: Disease detection and management might benefit from external imaging of disease gene mRNAs. Previously we designed molecular imaging nanoparticles (MINs) based on peptide nucleic acids complementary to cancer gene mRNAs. The MINs included contrast agents and analogs of insulin-like growth factor 1 (IGF-1). Analysis of MIN tumor uptake data showed stronger binding in tumors than in surrounding tissues. We hypothesized that MINs with an IGF-1 analog stay in circulation by binding to IGF-binding proteins. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…59 In any case, most, if not all, investigators incorporate partition coefficients into their nano PBPK models. 10,[17][18][19][20][21][22][24][25][26][27] Here, we found that at least in the case of PAA-PEG, PAA, and gold NPs, the biokinetics cannot be accurately described without introducing a P factor and a similar conclusion was reached by Lin et al 25 The exchange of NPs between blood and organs is strongly influenced by the ability to cross the endothelium. This endothelial permeability varies between organs as a result of differences in the degree of fenestration, as well as phagocytic capacity.…”
supporting
confidence: 71%
“…59 In any case, most, if not all, investigators incorporate partition coefficients into their nano PBPK models. 10,[17][18][19][20][21][22][24][25][26][27] Here, we found that at least in the case of PAA-PEG, PAA, and gold NPs, the biokinetics cannot be accurately described without introducing a P factor and a similar conclusion was reached by Lin et al 25 The exchange of NPs between blood and organs is strongly influenced by the ability to cross the endothelium. This endothelial permeability varies between organs as a result of differences in the degree of fenestration, as well as phagocytic capacity.…”
supporting
confidence: 71%
“…Typical preclinical tumor models average data across multiple animals to characterize biodistribution and pharmacokinetics, which are not translational approaches 39, 40 . In contrast, the molecular imaging approach used here can deliver quantitative spatio-temporal data within an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Through measurement of the cell area, volume and the partition coefficient, our method can isolate the fundamental uptake behavior that describes the effective overall process of cellular uptake. This can be used then, for example, in physiologically-based pharmacokinetic (PBPK) models [31]. In a typical PBPK model the various organs in the body are described by two compartments, a vascular and an extravascular compartment.…”
Section: Methodsmentioning
confidence: 99%
“…Further, we develop a simple, lumped mass transfer model that is used to extract the effective mass transfer coefficients from the quantitative uptake experiments and determination of the cell volume and surface area. As the mass transfer coefficient gives the fundamental rate of transport of a species independent of the area available for transport, these mass transfer coefficients can be used in physiologically-based pharmacokinetic models, e. g. [31]. Determining a mass transfer coefficient for a compound allows for a fundamental understanding of how the compound is internalized.…”
Section: Introductionmentioning
confidence: 99%